Assessment of historic brickwork under compression and comparison with available equations. (20th May 2019) - Boffill, Y.; Blanco, H.; Lombillo, I.; Villegas, L.
Highlights: Experimental tests of historic brickwork with aerial lime mortars were presented. Bricks pieces were acquired from demolition of different historic buildings. Aerial lime mortar behaviour was studied at different curing stages over two years. Adequate analytical formulations to evaluate the historic brickwork were identified. A new source of data for the assessment of historic brickwork is provided. Abstract: There is a lack of knowledge related to laboratory results on historic brick masonry made from lime mortars, given the time necessary to assure the mortar carbonation. Thus, this study contributes to the mechanic characterization, after 730 days of curing, of brickwork made from old solid clay bricks, acquired from building demolition, and two types of low-strength aerial lime mortars. Besides, the physical-mechanical characteristics of materials (bricks and mortars) were analysed over time. The experimental values were compared with analytical ones obtained using the main recommendations, research works, standards and the empirical equation obtained in this study. The most adequate analytical formulations are identified.